Interactive Storytelling Method Based on Local Wisdom to Improve the Empathy Abilities of Group B Children - Ni Putu Anik Dana Yanti; Luh Ayu Tirtayani (Universitas Pendidikan Ganesha, 2023)
The low ability of empathy possessed by young children makes them lack a sense of sharing, helping, and understanding other people's feelings. Based on the problems found, it is necessary to provide new methods for developing empathy skills in children. A method that can develop empathy skills is an interactive storytelling method based on local wisdom. This research aims to determine the effect of interactive storytelling methods based on local wisdom on empathy abilities in group B children. This type of research is a quasi-experiment with a non-equivalent control group design. The population in this study was all group B children, totaling 46 children. group B2, totaling 24 children, was the experimental group and group B1, totaling 22 children, was the control group. Data was collected using the observation method and then analyzed using the t-test. Based on the analysis results, there is a significant difference in abilities empathy between the children who were given interactive storytelling methods based on local wisdom and those who were not given interactive storytelling methods based on local wisdom. Based on the results of this research, the use of interactive storytelling methods based on local wisdom affects the empathy abilities of young children.